2004
DOI: 10.1124/jpet.103.061432
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Progesterone Prevent Disruption of Prepulse Inhibition by the Serotonin-1A Receptor Agonist 8-Hydroxy-2-dipropylaminotetralin

Abstract: The aim of the present study was to investigate the effect of estrogen and progesterone treatment on 5-hydroxytryptamine (serotonin)-1A (5-HT 1A ) receptor-mediated disruption of prepulse inhibition (PPI) of acoustic startle. The age-at-onset of schizophrenia is later in women than men, and it has been suggested that women may be protected from schizophrenia by the sex steroid hormone estrogen. 5-HT 1A receptors have been implicated in the development of schizophrenia and the action of antipsychotics. PPI is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 34 publications
7
66
1
Order By: Relevance
“…Furthermore, pretreatment with estrogen prevented this effect of buspirone. These results support our previous findings in female rats that 8-OH-DPAT-induced PPI deficits were prevented by estrogen treatment (Gogos and Van den Buuse, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, pretreatment with estrogen prevented this effect of buspirone. These results support our previous findings in female rats that 8-OH-DPAT-induced PPI deficits were prevented by estrogen treatment (Gogos and Van den Buuse, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…The present findings, together with our previous results (Gogos and Van den Buuse, 2004), suggest that estrogen may interact with 5-HT 1A receptors in the modulation of PPI in both rats and humans. It is unlikely that the 'interaction' involves estrogen altering 5-HT 1A receptor density or affinity, as estrogen treatment in ovariectomized rats does not alter 5-HT 1A receptor density or affinity in various brain regions, including the raphe nuclei, hippocampus, or prefrontal cortex (Flugge et al, 1999;Jackson and Etgen, 2001;Landry and Di Paolo, 2003).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although many studies showed that OVX is associated with poorer behavioral and cognitive performance, including tasks considered relevant to schizophrenia such as social interaction and object recognition (Barnes et al, 2006;Frye, 2001;Frye et al, 2006bFrye et al, , 2007Frye and Rhodes, 2006a;Paris and Frye, 2008), the study of the estrogen hypothesis using animal models of schizophrenia has been limited. Some support derives from studies showing that estrogen affects prepulse inhibition (PPI) (Gogos et al, 2009;Gogos and Van den Buuse, 2004;Koch, 1998;Vaillancourt et al, 2002;Van den Buuse and Eikelis, 2001), a measure of sensorimotor gating whose disruption is considered to model sensorimotor deficits in schizophrenia, as well as the response to the pro-psychotic drugs amphetamine and cocaine (Becker and Beer, 1986;Becker and Rudick, 1999;Earley and Leonard, 1978;Gibbs et al, 1998;Naik et al, 1978;Segarra et al, 2009). …”
Section: Introductionmentioning
confidence: 99%